IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP KORBAN PERKOSAAN DI KABUPATEN SIDRAP - Nasri, Muhammad (PETITUM, 2014)
An implementation of legal protection to implemented properly, similarly a criminal sanction to a rape perpetrators have not considered the impact or consequences of the victim of criminal act. The sanctions will not have a deterrent effect to perpetrators of rape criminal act and a good judge should punish the perpetrators of the criminal by including provision of compensation decide it parallel with a main criminal or independently if convict only threatened with criminal fine in single. As part of the criminal law policy not only from the point of reform-oriented policy approach (legal reform), but also the angle of value (law reform).